Analysis on Resin Starvation Issue in Carbon Fibre on J-Nose Panel - Abdul Razak, Azrie (IRC, 2018)
The author had been given a task in making study and analysis on resin starvation issue in carbon fibre on J-Nose panels. Throughout this project, the author would like to investigate the problem statement of this issue which were the surface of J-Nose panels after cure was found dry and brittle during visual inspection. Besides that, the defect panels also need to be rework in order to improve it and the rework process will increase the cost and time needed to produce a panel. There are a few objectives that the author wants to tackle in making this project. Firstly, the author would like to investigate the root cause of the defects found in aircraft panels through visual inspection. Next, after the root cause had been identified, the most suitable method in producing a better-quality panel will be proposed based on relevant studies and researches. Another objective which is important in this project is to reduce the cost, time and manpower consumed by the rework process.